Pharmacological and therapeutic effects of Peganum harmala and its main alkaloids - Moloudizargari, Milad (Medknow Publications & Media Pvt Ltd, 2013)
Wild Syrian rue (Peganum harmala L. family Zygophyllaceae) is well-known in Iran and various parts of this plant including, its seeds, bark, and root have been used as folk medicine. Recent years of research has demonstrated different pharmacological and therapeutic effects of P. harmala and its active alkaloids, especially harmine and harmaline. Analytical studies on the chemical composition of the plant show that the most important constituents of this plant are beta-carboline alkaloids such as harmalol, harmaline, and harmine. Harmine is the most studied among these naturally occurring alkaloids. In addition to P. harmala (Syrian rue), these beta-carbolines are present in many other plants such as Banisteria caapi and are used for the treatment of different diseases. This article reviews the traditional uses and pharmacological effects of total extract and individual active alkaloids of P. harmala (Syrian rue).